Adaptive root foraging strategies along a boreal-temperate forest gradient - Ostonen, Ivika; Truu, Marika; Helmisaari, Heljä-Sisko; Lukac, Martin; Borken, Werner; Vanguelova, Elena; Godbold, Douglas L; Lõhmus, Krista; Zang, Ulrich; Tedersoo, Leho; Preem, Jens-Konrad; Rosenvald, Katrin; et al. (The New phytologist, 2017)
The tree root-mycorhizosphere plays a key role in resource uptake, but also in the adaptation of forests to changing environments. The adaptive foraging mechanisms of ectomycorrhizal (EcM) and fine roots of Picea abies, Pinus sylvestris and Betula pendula were evaluated along a gradient from temperate to subarctic boreal forest (38 sites between latitudes 48°N and 69°N) in Europe. Variables describing tree resource uptake structures and processes (absorptive fine root biomass and morphology, nitrogen (N) concentration in absorptive roots, extramatrical mycelium (EMM) biomass, community structure of root-associated EcM fungi, soil and rhizosphere bacteria) were used to analyse relationships between root system functional traits and climate, soil and stand characteristics. Absorptive fine root biomass per stand basal area increased significantly from temperate to boreal forests, coinciding with longer and thinner root tips with higher tissue density, smaller EMM biomass per root length and a shift in soil microbial community structure. The soil carbon (C) : N ratio was found to explain most of the variability in absorptive fine root and EMM biomass, root tissue density, N concentration and rhizosphere bacterial community structure. We suggest a concept of absorptive fine root foraging strategies involving both qualitative and quantitative changes in the root-mycorrhiza-bacteria continuum along climate and soil C : N gradients.
Keywords: biologické modely; Europe; Geography; soil C : N ratio; Nitrogen; boreal and temperate forests; Biomass; Taiga; Rhizosphere; root morphology; bříza; Models, Biological; Evropa; Betula; rhizosféra; climate gradient; fyziologická adaptace; zeměpis; půdní mikrobiologie; soil and rhizosphere bacteria; mykorhiza; fine and ectomycorrhizal root biomass; root foraging; Mycorrhizae; Mycelium; Plant Roots; mycelium; Bacteria; Soil Microbiology; Adaptation, Physiological; tajga; Carbon; uhlík; biomasa; kořeny rostlin; ectomycorrhizal (EcM) mycelium; dusík